2020
DOI: 10.3390/systems8010001
|View full text |Cite
|
Sign up to set email alerts
|

Production Strategy Development: Simulation of Dependencies Using Recurrent Fuzzy Systems

Abstract: New and unsaturated markets are predominantly located in countries with low incomes. To successfully establish businesses in these new markets, an increasing globalization of value creation is necessary. The integration of these new markets is challenged by their dynamics, turbulence and regulation. Above all, an initially low and volatile demand as well as high barriers for market entry must be counteracted by economical small-series production. As market development is a major challenge for Small and Medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This study summarizes fields of application and the advantages and disadvantages of MCDMs. Moreover, we follow the argumentation in Brönner et al [34], who, based on Verlasquez and Hester [33], have evaluated the MCDM concerning their ability to map cause-effects, the need for exact knowledge of the system, the expandability of the database, and the option of weighting dependencies. They have concluded that a fuzzy logic-based solution best meets these requirements.…”
Section: Multicriteria Decision Methodsmentioning
confidence: 99%
“…This study summarizes fields of application and the advantages and disadvantages of MCDMs. Moreover, we follow the argumentation in Brönner et al [34], who, based on Verlasquez and Hester [33], have evaluated the MCDM concerning their ability to map cause-effects, the need for exact knowledge of the system, the expandability of the database, and the option of weighting dependencies. They have concluded that a fuzzy logic-based solution best meets these requirements.…”
Section: Multicriteria Decision Methodsmentioning
confidence: 99%
“…The influence of these strategies on the effective planning and management of production capacity is expressed in ensuring coordination of the production function with the other functional units for making tactical and strategic decisions, with the help of which the industrial enterprise to provide and maintain a competitive advantage. (Swamidass, 2000), (Brönner et al, 2020) Resource planning. This is a long and strictly specific process, including identifying the current state of the industrial enterprise, setting specific goals and objectives, developing a sequence of activities for their implementation and execution, analysis of the results and receiving feedback based on which determines follow-up actions for improvement and upgrading.…”
Section: Effective Planning and Management Of Production Capacity -Nature And Characteristicsmentioning
confidence: 99%
“…However, these categories are by no means to be regarded as isolated but are much more in context and interrelate with each other. For example, the infrastructure is directly related to the supplier structures [103]. The number of nominations depends on the concentration of authors within their publication on a region and not on their attempt to present the challenges holistically.…”
Section: Conclusion Of the Literature Researchmentioning
confidence: 99%